Hubungan Antara Citra Tubuh (Body Image) dengan Kecemasan Sosial Pada Remaja Perempuan - Mahatvamawati Milinia Rizqiyah; Effy Wardati Maryam (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
This research is undermined by the phenomenon of adolescents experiencing high social anxiety and the perception of body images that have become stereotyped. The study aims to find out the relationship between body image and social anxiety in teenage girls at Sidoarjo High School. This research uses quantitative research using correlational methods. Body imagery is used as a free variable, and social anxiety is used as a bound variable in this study. The research was conducted at Sidoarjo High School and used a sample of 270 people out of a total population of 1159 students using the Proportional Random Sampling technique. The data collection technique uses the Likert model for two psychological scales: a body image scale adopted from the Anisykurli scale based on the body image aspects presented by Cash, with a valid item of 24 and a reliability value of 0.923. And the social anxiety scale adopted from the Baihaqi scale is based on the social-anxiety aspect presented by La Greca and Lopez, with a valid item of 33 and a reliability value of 0.911. The hypothesis in this study is that there is a negative correlation between body image and social anxiety in high school girls in Sidoarjo. The data analysis used is Pearson's Product Moment Analysis, using correlation techniques using the JASP 16.0 for Windows program. This study produced a significant negative relationship between body image and social anxiety (p.001, r =-206). It is hoped that this study can provide information to future researchers and high school students about Sidoarjo-related body shape and negative judgment in social situations.